Adhaeribacter radiodurans sp. nov., isolated from the rhizospheric soil of Elymus tsukushiensis, a plant native to the Dokdo Islands, Republic of Korea. Issue 1 (17th January 2021) - Hwang, Ye-Ji; Son, Jin-Soo; Lee, Soo-Yeong; Kim, Min-Ji; Park, Jong Myong; Shin, Jae-Ho; Ghim, Sa-Youl
Abstract : KUDC8001 T was isolated from the rhizosperic soil of Elymus tsukushiensis in the Dokdo Islands, Republic of Korea. Strain KUDC8001 T was Gram-stain-negative, non-motile and rod-shaped. KUDC8001 T was catalase- and oxidase-positive. This strain is capable of growing at 4–37 °C and pH 7.0–8.0 and exhibited optimal growth at 25 °C and pH 7.0. It could be grown in R2A, nutrient agar and ISP2 agar plates. The cell width ranged from 0.7 to 1.0 µm, and length ranged from 2.5 to 5.5 µm. The genomic G+C content was 40.8 mol%. Phylogenetic analysis, based on 16S rRNA gene sequences, revealed that the strain KUDC8001 T belongs to the genus Adhaeribacter, which is most closely related to the strain A. pallidiroseus HMF7616 T (97.5%). The DNA relatedness of KUDC8001 T with the type strains of A. pallidiroseus HMF7616 T, A. swui 17 mud1-7 T and A. arboris HMF7605 T was ≤80.3 % based on average nucleotide identity calculations and ≤86.9 % based on average amino acid identity calculations. In silico DNA–DNA hybridization values of the strain KUDC8001 T with the most closely related strains were 22.1, 24.0 and 24.4 %. Based on its phenotypic, phylogenetic, genetic and chemotaxonomic features, the strain KUDC8001 T should be considered as a novel species in the genus Adhaeribacter, for which we have proposed the name Adhaeribacter radiodurans sp. nov. The type strain is KUDC8001 T (=KCTC 82078 T =CGMCC 1.18475 T ).